Drug retention, inactive disease and response rates in 1860 patients with axial spondyloarthritis initiating secukinumab treatment: routine care data from 13 registries in the EuroSpA collaboration. Issue 3 (19th September 2020) - Michelsen, Brigitte; Lindström, Ulf; Codreanu, Catalin; Ciurea, Adrian; Zavada, Jakub; Loft, Anne Gitte; Pombo-Suarez, Manuel; Onen, Fatos; Kvien, Tore K; Rotar, Ziga; Santos, Maria Jose; Iannone, Florenzo; et al.
Abstract : Objectives: To explore 6-month and 12-month secukinumab effectiveness in patients with axial spondyloarthritis (axSpA) overall, as well as across (1) number of previous biologic/targeted synthetic disease-modifying antirheumatic drugs (b/tsDMARDs), (2) time since diagnosis and (3) different European registries. Methods: Real-life data from 13 European registries participating in the European Spondyloarthritis Research Collaboration Network were pooled. Kaplan-Meier with log-rank test, Cox regression, χ² and logistic regression analyses were performed to assess 6-month and 12-month secukinumab retention, inactive disease/low-disease-activity states (Bath Ankylosing Spondylitis Disease Activity Index (BASDAI) <2/<4, Ankylosing Spondylitis Disease Activity Score (ASDAS) <1.3/<2.1) and response rates (BASDAI50, Assessment of Spondyloarthritis International Society (ASAS) 20/40, ASDAS clinically important improvement (ASDAS-CII) and ASDAS major improvement (ASDAS-MI)). Results: We included 1860 patients initiating secukinumab as part of routine care. Overall 6-month/12-month secukinumab retention rates were 82%/72%, with significant (p<0.001) differences between the registries (6-month: 70–93%, 12-month: 53–86%) and across number of previous b/tsDMARDs (b/tsDMARD-naïve: 90%/84%, 1 prior b/tsDMARD: 83%/73%, ≥2 prior b/tsDMARDs: 78%/66%). Overall 6-month/12-month BASDAI<4 were observed in 51%/51%, ASDAS<1.3 in 9%/11%, BASDAI50 in 53%/47%, ASAS40 in 28%/22%, ASDAS-CII in 49%/46% and ASDAS-MI in 25%/26% of the patients. All rates differed significantly across number of previous b/tsDMARDs, were numerically higher for b/tsDMARD-naïve patients and varied significantly across registries. Overall, time since diagnosis was not associated with secukinumab effectiveness. Conclusions: In this study of 1860 patients from 13 European countries, we present the first comprehensive real-life data on effectiveness of secukinumab in patients with axSpA. Overall, secukinumab retention rates after 6 and 12 months of treatment were high. Secukinumab effectiveness was consistently better for bionaïve patients, independent of time since diagnosis and differed across the European countries.